Phytic Acid: Properties and Potential Applications in Dentistry - Nassar, Mohannad; Nassar, Rania; Maki, Husain; Al-Yagoob, Abdullah; Hachim, Mahmood; Senok, Abiola; Williams, David; Hiraishi, Noriko (Frontiers in Materials, 2021)
Inositol hexaphosphate (IP6) is the most abundant inositol phosphate in nature and an essential molecule for different biological functions. IP6 has a unique structure granting it distinctive properties; the high negative charge density provides IP6 with an immense chelating ability and valuable antioxidant properties. IP6 is also simple and cost-effective to produce. These features have attracted researchers and entrepreneurs to further study IP6 for a wide variety of applications in areas such as pharmaceutical, food and chemical industries, medicine, pharmacy, nutrition, and dentistry. The interest in IP6 in the dental field unfolded many decades ago following identification of a cariostatic ability and a positive impact on reducing enamel dissolution. Subsequently, IP6’s anti-plaque, anti-calculus and cement-forming properties have been investigated. Despite encouraging findings, there was a phase of decreased attention to IP6 which slowed down research progress. However, the potential use of IP6 has recently been revisited through several publications that provided deeper understanding to its mechanisms of action in the aforementioned applications. Studies have also explored new applications in endodontics, adhesive, preventive and regenerative dentistry, and IP6’s role in improving the characteristics and performance of dental materials. Evidence of the merits of IP6 in dentistry is now substantial, and this narrative review presents and discusses the different applications proposed in the literature and gives insight of future use of IP6 in the fields of orthodontics, implant and pediatric dentistry.